Using Emr In A Corporate Hospital: Healthcare Providers Perspective From Bangladesh - Hossain, Md Emam; Riaz, Baizid Khoorshid; Islam, Md Ziaul (Journal of Preventive and Social Medicine, 2024)
Background: An Electronic Medical Record (EMR) is an essential tool for delivering high-quality healthcare in a hospital. In recent years, hospitals have increased their investment in EMRs to improve the level of integrated management of information. The purpose of this study was to explore the perspectives of using EMR among healthcare providers (HCPs) in a corporate hospital in Bangladesh. Methods: This cross-sectional study was conducted among 153 HCPs (doctors, nurses, lab technicians, drug dispensers, billing managers, and administrative personnel) who have access to EMR and working in a selected corporate hospital of Dhaka city. The study period was January to December 2019. HCPs were selected by convenience sampling technique. Data were collected by face-to-face interview using semi structured questionnaire. Data analysis was done by IBM SPSS software. Ethical issues were maintained strictly. Result: Study revealed that 59.5% HCPs were in the age group of 18-29 years with the mean age being 29.26 (±7.58) years. Only 32.7% HCPs had previous experience of using this type of software before working in the current hospital and 62.7% got technical training on EMR within the current hospital. The majority (81.7%) of the HCPs found that the technical training was effective for using the EMR software. The difficulty of using EMR was significantly associated with the age (p<0.001), gender (p<0.001), professional status (p<0.001) and highest level of education (p<0.001) of the HCPs. HCPs ability to overcome job related challenges was significantly associated with the professional status of them (p<0.001). HCPs perception regarding effectiveness of EMR was found significantly associated with their place of technical training (p=0.004) and duration of the training (p=0.012). Conclusion: EMR can be a helpful tool for the health service providers to provider health services at the corporate hospitals. Digital literacy need to be increased among the HCPs to ensure effective use of EMRs. Regular maintenance and upgrades of the technology infrastructure are necessary for advanced record-keeping and quality service. JOPSOM 2021; 41(2):12-19